Assessing the Impacts of Climate Change on Meteorology and Air Stagnation in China Using a Dynamical Downscaling Method - Hu, Anqi; Xie, Xiaodong; Gong, Kangjia; Hou, Yuhui; Zhao, Zhan; Hu, Jianlin (Frontiers in Environmental Science, 2022)
This study utilizes the Weather Research and Forecasting (WRF) model with a higher resolution (36 km × 36 km) to dynamically downscale the Community Earth System Model (CESM) results forced by the three RCP scenarios (RCP4.5, RCP6.0, and RCP 8.5) over China to compare the meteorological fields during the present (2006–2015) and future (2046–2055) climatological periods. An appropriate air stagnation judgment index was selected to explore the effect of climate change on air quality-related meteorological conditions. The results show that occurrence of wintertime air stagnation over China in the middle of this century (2046–2055) will reduce slightly, with the largest reduction in the RCP8.5 scenario (−4 times). However, the long-lasting air stagnation events are projected to increase in the future, and this increasing trend is more obvious under the RCP8.5 scenario. The projected increase of the long-lasting ASE in different regions of China ranges from 3 to 11 times. Among them, Central China has the largest increase, followed by East and Northeast China, while South China has the lowest increase. Our results indicate that we should pay more attention to the extreme pollution events that may be caused by long-lasting air stagnation events in the future.